LOW NOISE CONTROL ALGORITHM FOR HYDRAULIC SYSTEMS (2015)
A hydraulic pump radiant noise reduction method for a forklift or other work machine is disclosed. The method includes initiating a noise control algorithm that is enabled during periods when the displacement of the hydraulic pump remains in the zero displacement position and an operator is not demanding flow from any of the hydraulic branch circuits. When the noise control algorithm is enabled, the control valve assembly associated with the hydraulic branch circuit having the lowest hydraulic fluid pressure in relation to the hydraulic fluid pressures of all other hydraulic branch circuits is opened while the remaining control valve assemblies are in held or placed in a closed position. In an alternative embodiment, a drain valve assembly is provided that is opened when the noise control algorithm is activated.